DEBTOR PROTECTION IN PERSPECTIVE OF PANCASILA JUSTICE VALUE ON SEPARATIC CREDITOR EXECUTIONS - Widhi Handoko (UNISSULA, 2021)
The execution of the execution by separatist creditors without going through court adjudication as stipulated in Article 55 and Article 56 of Act No. 37 of 2004 is contrary to Pancasila justice. The method used in this research is a non-doctrinal method. Based on the data obtained, it can be seen that the implementation of bankruptcy executions as regulated in Article 55 and Article 56 of Act No. 37 of 2004 prioritizes the interests of separatist creditors, this is further complicated by the existence of a legal culture that shows that bankruptcy executions are guaranteed with mortgage rights. Without having to go through an amazing in court, the meaning of the debtor's insolvency should be an examination in court or through amazing regarding the debtor's ability to pay off his debt, not solely based on the analysis and views of the separatist creditors. This is implicitly based on Article 28D of the 1945 Constitution of the Republic of Indonesia and automatically contradicts the values of Pancasila social justice. This means that in the legal policy of bankruptcy execution, it must be able to create a balance of protection of rights between creditors and debtors, by the view of appreciation for human values or human rights awards in the form of equality before the law to be able to realize a just bankruptcy execution that can protect the interests of separatist creditors while protecting debtors from losses resulting from bankruptcy.